2019
DOI: 10.1002/jor.24453
|View full text |Cite
|
Sign up to set email alerts
|

In‐Room Ultraviolet Air Filtration Units Reduce Airborne Particles During Total Joint Arthroplasty

Abstract: Reducing airborne bioburden in total joint arthroplasty (TJA) is of critical importance. The efficacy of crystalline ultraviolet-C (C-UVC) filtration in reducing bioburden in a dynamic operating room (OR) environment has not been evaluated. We assessed whether C-UVC filtration reduced (i) total particle counts (TPC); (ii) viable particle counts (VPC); and (iii) colony-forming units (CFUs). Fifty primary TJA cases were performed in a positive-pressure OR; 25 cases with the C-UVC unit and 25 cases without. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
(49 reference statements)
1
16
0
1
Order By: Relevance
“…Repetition of the study in different ORs and with different surgical procedures would enable better characterization of the device's effects. However, like previous studies [18] , [19] , the present study showed a substantial reduction in the number of particles. Finally, the number of theatre staff, the air change cycle and pressure differences with respect to outside are other risk factors that could have a confounding effect on the final results.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Repetition of the study in different ORs and with different surgical procedures would enable better characterization of the device's effects. However, like previous studies [18] , [19] , the present study showed a substantial reduction in the number of particles. Finally, the number of theatre staff, the air change cycle and pressure differences with respect to outside are other risk factors that could have a confounding effect on the final results.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies showed the effectiveness of the device in reducing and keeping down particle count [18] , [19] , but particle sizes were not differentiated. Our study analyzed variations in particle size and particle sampling in several points in the OR.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sendo assim, quanto menor for o comprimento de onda, mais energética será a radiação transportada por ela. A radiação ultravioleta UV representa parte do espectro eletromagnético com o comprimento de onda menor que o da luz violeta, ou seja, uma faixa imediatamente mais energética do que a luz visível [16][17][18] . Devido à quantidade de energia transportada nas ondas UV, elas estão no limite denominado Região ionizante do espectro eletromagnético, isso indica que as ondas possuem condições de formar íons, o que significa ter condições de causar danos a moléculas de DNA 19,20 .…”
Section: Uvcunclassified
“…Similar systems exists that use ultraviolet light to sterilise air particles and reduce the rate of hospital-acquired infections 21 22. There are though few peer-reviewed articles regarding air purification.…”
Section: Introductionmentioning
confidence: 99%